2019
DOI: 10.1016/j.jenvman.2019.109317
|View full text |Cite
|
Sign up to set email alerts
|

Flood risk management in Sint Maarten – A coupled agent-based and flood modelling method

Abstract: Disaster risk reduction is a major concern of small island developing states. Measures to reduce risk should not only be based on the magnitude of physical hazard, but also on the exposure and vulnerability of communities. In this article, we examine flood risk management policies in the Caribbean island of Sint Maarten using coupled agent-based and flood models. The agent-based model is used to model actors' behaviour in relation to urban building development and policies that are designed to reduce flood haz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
69
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(71 citation statements)
references
References 22 publications
1
69
0
1
Order By: Relevance
“…Tonn and Guikema (2017) investigated different mitigation strategies at community and individual levels using statistical flood-level data. Abebe et al (2018Abebe et al ( , 2019) developed a new framework for integrating a hydraulic model into an ABM to represent individual and institutional decision making during flooding.…”
Section: Introductionmentioning
confidence: 99%
“…Tonn and Guikema (2017) investigated different mitigation strategies at community and individual levels using statistical flood-level data. Abebe et al (2018Abebe et al ( , 2019) developed a new framework for integrating a hydraulic model into an ABM to represent individual and institutional decision making during flooding.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, this paper extends two studies presented in Birkholz (2014) and Abebe et al (2019b). Birkholz qualitatively explored PMT to study household flood preparedness behaviour in the German city of Hamburg.…”
Section: Introductionmentioning
confidence: 51%
“…Adding local knowledge of flood risk management (FRM) issues and using other data sources, we extended the previous work by developing a simulation model that could support decision-making. Furthermore, the study has extended other prior works (Abebe et al, 2019b;Erdlenbruch and Bonté, 2018;Haer et al, 2016) to study human-flood interaction better and to gain new policy insights. With all the extensions, we have demonstrated that coupled ABM and flood models, together with a behavioural model, can potentially be used as decision support tools to examine the role of household adaptation measures in FRM.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Alternatively, location-specific fixed flood maps (Dubbelboer et al, 2017;Haer et al, 2017) are used for different return periods, for example, 1:100 flood. Finally, there are examples of articles belonging to the SH group that employ hydrologic models (Abebe et al, 2019a(Abebe et al, , 2019bHaer et al, 2019Haer et al, , 2020Löwe et al, 2017;McNamara & Keeler, 2013;Michaelis et al, 2020). Despite the increased complexity of coupling engineering and socio-economic models, hydrologic models' presence establishes a two-way feedback between human and natural systems.…”
Section: Risk Components In Flood-abmsmentioning
confidence: 99%